2021
DOI: 10.5897/ajb2020.17291
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, physicochemical and antimicrobial properties of rhenium (I) tricarbonyl complexes of isatin Schiff bases

Abstract: The Schiff base of isatin and sulphanilamide (L1; C 14 H 11 N 3 O 3 S) was prepared and reacted with Re(CO) 5 X (X = Cl and Br) in toluene to give [Re(C 14 H 10 N 2 O)(CO) 3 X] (X = Cl, 1 and X = Br, 2). The prepared Schiff base of isatin and 4-methoxyaniline (L2; C 15 H 12 N 2 O 2 ) was reacted with Re(CO) 5 X in toluene to give [Re(C 14 H 10 N 2 O)(CO) 3 X], where X = Cl, 3 and X = Br, 4. L2 and Re(CO) 5 Br were refluxed in dry toluene under nitrogen and recrystallized to give [Re(C 15 H 12 N 2 O 2 )(CO) 3 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…We can see from Fig ( 2) that there is a significant decrease in the corrosion rate and an increase in the inhibition efficiency as the concentration of the inhibitor is increased. This supports that the used inhibitor gets adsorbed on the metal surface and protects it by forming a protective layer [5][6][7].…”
Section: Effect Of Concentrationsupporting
confidence: 62%
See 3 more Smart Citations
“…We can see from Fig ( 2) that there is a significant decrease in the corrosion rate and an increase in the inhibition efficiency as the concentration of the inhibitor is increased. This supports that the used inhibitor gets adsorbed on the metal surface and protects it by forming a protective layer [5][6][7].…”
Section: Effect Of Concentrationsupporting
confidence: 62%
“…The protective layer formed on the metal surface was studied by using Electron dispersion X-ray analysis (EDAX). From Table (6), it can be observed that before immersion of a mild steel sample in 0.1 N HCl solution, the Fe content was around 90%. But after immersion in 0.1 N HCl for 24 hours the Fe content decreased to around 63%.…”
Section: Edax Analysismentioning
confidence: 99%
See 2 more Smart Citations